If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+1)+3=8(2x-2)-7
We move all terms to the left:
2(x+1)+3-(8(2x-2)-7)=0
We multiply parentheses
2x-(8(2x-2)-7)+2+3=0
We calculate terms in parentheses: -(8(2x-2)-7), so:We add all the numbers together, and all the variables
8(2x-2)-7
We multiply parentheses
16x-16-7
We add all the numbers together, and all the variables
16x-23
Back to the equation:
-(16x-23)
2x-(16x-23)+5=0
We get rid of parentheses
2x-16x+23+5=0
We add all the numbers together, and all the variables
-14x+28=0
We move all terms containing x to the left, all other terms to the right
-14x=-28
x=-28/-14
x=+2
| 1/10x-2/5=7/20 | | 3x-10+5x=50 | | -7y=-6y+3 | | -10x+145=10x-35 | | I(n)=2+3.5n | | 5.3(x–7)=27 | | -2(7x+7)=-14x+14 | | -14=p-7 | | 8r-8+3=19 | | 64=12t-5t^2 | | -(10/3)=13x | | |5x+4|=41 | | 22=3x+2+2x | | 7(2x+3)=77x+84 | | -8+5m=-23 | | 11/3=17/2x | | I(n)=3.5-2n | | 5x+5-10=55 | | 10-(6-6n)+16n=-8+18(n+1) | | 8+14z=–7+17z | | 4x+4x=4+4 | | 4x=4+4+4 | | 7+x1=57 | | 4+12x=13x-2 | | 6(x+2)=4(2x-1) | | t=25+8.25 | | -21=9-3b | | 22=7-3c | | x/2+30=96 | | (−10.5+m)/11.57=−2.748 | | 12r-3(r+5)=4(3r-6)-3 | | 4+4+4x=4x |